(untitled) (Biological Sciences - PJSIR, 1998)
The values of rl and r2 calculated by EVM method for each copolymer system were taken from our previous work (Munsif and Kaim 1993 and 1994; Munsif etall994; Munsifand Kaim 1995 and 1996). The Q2 and e values for styrene (sty) have been taken as that of Alfrey and Price (1947) (QI = 1.0 and e = -0.80) for calculating the Q2 and e2 values.